Improving strength and power - Mason, Paul (London Wayland, 2010)
While all sports use a combination of flexibility, endurance, strength and speed, one of these is usually dominates over the others, depending on the sport. This series introduces each of these physical qualities by way of the sports they are most important for. The series includes: Profiles of sportspeople whose sport fits into the category - how they train and how this is reflected in their physique Training programmes Cross-training activities Nutrition and recipes Cross-curricular elements covering science, food technology and sport.
Include Color Illustrations and Color
Keywords: Muscle strength -- Physical education and training -- Physical fitness